Tres especies nuevas de Bursera (Burseraceae) de la región costera del occidente de México - Rzedowski, Jerzy; Calderón de Rzedowski, Graciela (Instituto de Ecología, A.C., 2000)
Bursera palaciosii, B. ribana and B. vazquezyanesii are described as new species and illustrated. All seem to be restricted to the littoral belt of the Mexican state of Jalisco and some adjacent areas. The first one is probably related to B. staphyleoides McVaugh & Rzed., the second one to B. laxiflora S. Watson and the third to B. denticulata McVaugh & Rzed.